Blockchain based Efficient and Secure Peer-to-Peer Distributed IoT Network for Non-Trusting Device-to-Device Communication - Sharma, Rajesh Kumar; Pippal, Ravi Singh (Informatica, 2023)
The security and privacy issues in the Internet of Things (IoT) is a mandatory process and also a challenging task for researchers. Blockchain technology enhanced and motivated the recent security parameters and it has been validating various technical sectors since its inception. In this paper, a peer-to-peer distributed IoT network is presented where non-trusting devices can interact with the other devices without a trustworthy inter-mediator using blockchain technique, in automated veriable mode. Major implementation issues to deploy blockchain in the IoT network is pointed out in this paper. The model presents modern blockchain technique to surpass the traditional security system in ecient and secure IoT deployment at various conditions. Finally, to validate the signication of blockchain in IoT network, the avalanche effect is calculated and compared with Triple-DES, AES and Blowsh cryptographic algorithms for non-trusting device-to-device communications and transactions. The result presents signicant output changes in hash for blockchain-IoT integrated model as compared to other cryptographic algorithms. Conclusively, blockchain in IoT network can make a remarkable impact across various industrial and business applications.